Integration of oral health into primary care: the policy and practice - Gaffar, Balgis (fi=Turun yliopisto|en=University of Turku|, 2025)
This study evaluated global oral health policy integration, interdisciplinary practices, and the effectiveness of an educational intervention among healthcare providers in Saudi Arabia. In phase I, data was collected from 60 countries to assess oral health policies. In phase II, 1,398 healthcare professionals from Saudi Arabia were surveyed to examine interdisciplinary practices, and 525 nurses were assessed for attitudes and practices in phase III. In phase IV, an educational intervention targeting nurses and physicians was evaluated for its impact on oral health knowledge and beliefs. The study found that 55.2% of the countries had formal oral health policies for children, with 54% incorporating oral health into general health policies. Of the countries, 49.4% had programs targeting disadvantaged populations and 48.3% included dental care in universal health coverage. Interprofessional collaboration was encouraged in 53.3% of countries, with significant regional variation. In Saudi Arabia, the mean oral health knowledge score among the healthcare professionals was 7.1 ± 2.1 (out of 13), with physicians scoring the highest and nurses the lowest scores. Attitudes towards oral health care were generally positive. Among the nurses, 70.3% responded to patients’ oral health concerns and 47.1% conducted screenings, while 19.7% provided oral health education. The key barriers included lack of training (61.7%) and heavy workloads (53.8%). The educational intervention significantly improved the knowledge scores (mean post-intervention: 20.3 ± 3.6 for the video participants, 18.4 ± 4.2 for the brochure participants, p < 0.001), while belief scores remained unchanged. Global and national gaps persist in oral health policy integration and interdisciplinary practices. The educational intervention effectively improved oral health knowledge but had limited impact on beliefs. Enhanced training, policy support, and interprofessional collaboration are essential to advancing oral health integration.

Tässä tutkimuksessa arvioitiin maailmanlaajuisesti suun terveyspolitiikan integraa-tiota, monitieteisiä käytäntöjä ja terveydenhuollon ammattilaisten koulutustoimien tehokkuutta Saudi Arabiassa. Vaiheessa I kerättiin tietoja 60 maasta suun terveyspolitiikan arvioimiseksi. Vaiheessa II kyselyyn osallistui 1398 terveydenhuollon ammattilaista Saudi-Arabiassa monitieteellisten käytäntöjen selvittämiseksi ja vaiheessa III 525 sairaanhoitajan asenteita ja käytäntöjä. Vaiheessa IV arvioitiin sairaanhoitajille ja lääkäreille suunnatun koulutusintervention vaikutusta suun terveyteen liittyvään tietoon ja uskomuksiin. Maailmanlaajuisesti 55,2 %:lla maista oli virallinen lasten suun terveyspolitiikka ja 54 %:lla maista suun terveydenhuolto sisällytettiin yleiseen terveyspolitiikkaan. Maista 49,4 %:lla oli ohjelmia, jotka oli suunnattu heikommassa asemassa oleville väestöryhmille ja 48,3 % sisällytti hammashoidon yleiseen terveydenhuoltoon. Moniammatillista yhteistyötä kannustettiin 53,3 %:ssa maista ja alueelliset erot vaihtelivat merkittävästi. Saudi-Arabiassa terveydenhuollon ammattilaisten keskimääräinen suun tervey-den tietopistemäärä oli 7,1 ± 2,1 (13:sta); lääkärit saivat korkeimmat ja sairaan-hoitajat alhaisimmat pisteet. Asenteet suun terveyttä kohtaan olivat yleensä posi-tiivisia. Sairaanhoitajista 70,3 % vastasi potilaiden suun terveyden kysymyksiin, 47,1 % teki seulontatutkimuksia ja 19,7 % antoi suun terveyskasvatusta. Keskeisiä esteitä olivat koulutuksen puute (61,7 %) ja raskaat työmäärät (53,8 %). Koulutusinterventio paransi merkittävästi suun terveyden tietopisteitä (keskiarvo interventioon osallistuneilla: 20,3 ± 3,6 videoryhmässä ja 18,4 ± 4,2 esiteryhmässä; p < 0,001). Uskomuspisteet pysyivät ennallaan. Suuterveyspolitiikan integroinnissa ja monitieteisissä käytännöissä on edelleen maailmanlaajuisia ja kansallisia puutteita. Koulutusinterventio paransi merkittävästi tietämystä suuterveydestä, mutta sillä oli rajallinen vaikutus uskomuksiin. Tehos-tettu koulutus, poliittinen tuki ja ammattien välinen yhteistyö ovat välttämättömiä suun terveyden integroinnin edistämiseksi.